Comparative study of the functional outcome of semitendinosus graft versus peroneus longus graft in arthroscopic reconstruction surgeries of anterior cruciate ligament - Ambulgekar, Rajesh K.; Chhabda, Gurneet Kaur; Malu, Mukesh; Sangnod, Pradeep (International Journal of Research in Orthopaedics, 2023)
Background: ACL disruption is the commonest ligamentous knee injury among active adults, invariably leading to changes in knee kinematics which are most likely to result in secondary degenerative changes and long-term functional impairment. Thus, due to the ACL’s crucial role as the primary restraint against anterior tibial translation, its reconstruction using varying graft options are being extensively studied for better functional outcome. Methods: In this prospective study, we analysed 30 patients having ACL tear (clinically and radiographically) and treated with arthroscopic reconstruction of ACL. Among these, 15 cases were operated using semitendinosus graft and 15 cases by using peroneus longus tendon graft. The study was conducted in a tertiary care hospital from January 2021 to June 2022 with minimum follow up of 6 months and maximum follow up of 15 months. Results: Mean Lysholm score (post op) in Group ST was 90.6±3.18 and in Group PLT was 92.2±2.65. The Lysholm Score and IKDC grading between the two groups was comparable and showed no significant difference. Post-Op laxity assessed using the Lachman’s grading showed normal findings in 70% patients, and of the remaining 30% (9 patients), 5 patients from ST group and 4 patients from PLT group showed 1+ laxity at follow up examination. Conclusions: Arthroscopy assisted ACL reconstruction with peroneus longus tendon autograft provides a steady knee, reduces postoperative donor site morbidity and enables early rehabilitation, similar to the traditional semitendinosus tendon autograft.